Development and effect of the body balance to the pressure sensor monitoring - Jia, Tanzhen; Zulkifli, Ahmad@Manap; Muhammad Amirul Afiq, Saidi; Mohamad Zairi, Baharom (Institution of Engineering and Technology, 2022)
Plantar pressure can be formed during the static and dynamic motion. It calculated by the force divided to the contact surface area of the foot and the ground. The body balance training device is functioned to help people measure the effectiveness of physiotherapy treatment in rehabilitation pro-cess. Therefore, the objective of this study is to develop a body balance de-vice which equipped with the pressure sensor system. The design characteristics such as type of conductive layer used, resistor value, velostat size and sensors arrangement were considered in determining an optimum setting. In order to validate the device, footprint testing was performed to identify the contact surface area for sensor placement under the insole. Then, it was compared with the data obtained from the sensors according to the similar arrangement on the footprint. For real-time monitoring, a foot model was developed consist of the RGB led to indicates the level of pressure. This monitoring method is benefit for the rehabilitation as well as custom shoe selector which provided the characteristic of foot plantar.